Trends and inequalities in the surgical management of ureteric calculi in the USA. (21st November 2013) - Seklehner, Stephan; Laudano, Melissa A.; Jamzadeh, Asha; Del Pizzo, Joseph J.; Chughtai, Bilal; Lee, Richard K.
<x xml:space="preserve">Abstract</x> Objective To assess trends in the surgical management of ureteric calculi over a 10‐year period. Materials and Methods An analysis of the 5% Medicare Public Use Files, from 2001, 2004, 2007 and 2010, was performed to assess the use of ureteroscopy (URS), extracorporal shockwave lithotripsy (ESWL) and ureterolithotomy (UL) in treating ureteric calculi. Patients were identified using International Classification of Diseases 9th edition (Clinical Modification) and Current Procedure Terminology codes. Statistical analyses using the Fisher and chi‐squared tests, and multivariate logistic regression analysis (dependent variables: URS, ESWL, UL, treatment, no treatment; independent variables: age, gender, ethnicity, geography and year of treatment) were performed. Results A total of 299 920 patients with ureteric calculi were identified. Of these, 115 200 underwent surgery. Men (odds ratio [OR] = 1.15, P < 0.001) were more likely, while patients from ethnic minorities (OR = 0.84, P = 0.004) were less likely to be treated. Patients in the West of the USA were also less likely to be treated (OR = 0.76, P < 0.001) as were patients aged <65 or >84 years old (P = 0.29). The predominant surgical approach was URS (65.2%), followed by ESWL (33.6%) and UL (1.2%). The use of URS increased over time, while the use of ESWL and UL declined. Women (OR = 1.25, P < 0.001) were more likely to undergo URS. Patients in the South of the USA (OR = 1.51, P < 0.001) and patients from ethnic minorities were more likely to undergo ESWL (OR = 1.23, P = 0.03). Conclusions The surgical treatment of ureteric calculi changed significantly between 2001 and 2010. The use of URS expanded at the expense of ESWL and UL. Multiple inequalities existed in overall surgical treatment rates and in the choice of treatment; age, gender, ethnicity and geography influenced both whether patients underwent surgical intervention and the type of surgical approach used.